Primer in Patient Safety Concepts: Simulation Case-Based Training for Pediatric Residents and Fellows - Ayesha Mirza; Jeffrey Winer; Matthew Garber; Kartikeya Makker; Nizar Maraqa; Rana Alissa (Association of American Medical Colleges, 2018)
Introduction Health care quality and patient safety remain one of the core areas of focus for the Accreditation Council for Graduate Medical Education. In addition to using the traditional approach to teaching patient safety, disclosure of a safety event and introduction to the concepts of just culture and safely doing less add a unique perspective to our module. Methods This 4-hour learning activity was conducted using a formal PowerPoint presentation, simulation, and interactive discussion/debriefing. The presentation reviewed safety concepts and introduced learners to the concepts of just culture and safely doing less. The first case was a standard scenario in which participants assessed a sick but stable child and evaluated the use of premature closure bias that might preclude them from making the correct diagnosis. The second case represented disclosure of a medical error. Participants were evaluated on their communication/professionalism skills and challenged to discover overuse as one of the root causes of medication error. Pre- and posttest surveys were used for learner evaluation. Results Participants showed significant improvement on content-based questions, increasing from 51.7% to 69.3% correct (p < .001). After Bonferroni correction, only the question on overdiagnosis showed significant improvement (p = .001). Participants reported significantly increased confidence in all areas evaluated (p < .001). Discussion Participants placed high value on the workshop. The question on overdiagnosis showed significant improvement on the posttest. The concepts of patient safety, just culture, and safely doing less can be introduced to learners at a formative stage in their career through simulation.